2012
DOI: 10.1371/journal.pone.0030873
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CCL5 Expression in Smooth Muscle Cells Following Arterial Injury

Abstract: Chemokines play a crucial role in inflammation and in the pathophysiology of atherosclerosis by recruiting inflammatory immune cells to the endothelium. Chemokine CCL5 has been shown to be involved in atherosclerosis progression. However, little is known about how CCL5 is regulated in vascular smooth muscle cells. In this study we report that CCL5 mRNA expression was induced and peaked in aorta at day 7 and then declined after balloon artery injury, whereas IP-10 and MCP-1 mRNA expression were induced and peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 53 publications
1
17
1
Order By: Relevance
“…We have previously reported that IRF-1 was key not only in driving steroid-resistant genes in ASM cells (25) but also in impairing ASM sensitivity to GC by reducing GRa transactivation function (32). Whether IRF-1 plays a role in the currently investigated GC chemokines in GCresistant conditions has not been investigated, although limited evidence indicates a role of IRF-1 in CCL5 expression in vascular smooth muscle (42) and bronchial epithelial cells (43). Our silencing experiments confirmed the key role of IRF-1 in ASM cells in driving the expression of GC-resistant chemokines via transcriptional (CCL5) and posttranscriptional mechanisms (CX3CL1).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that IRF-1 was key not only in driving steroid-resistant genes in ASM cells (25) but also in impairing ASM sensitivity to GC by reducing GRa transactivation function (32). Whether IRF-1 plays a role in the currently investigated GC chemokines in GCresistant conditions has not been investigated, although limited evidence indicates a role of IRF-1 in CCL5 expression in vascular smooth muscle (42) and bronchial epithelial cells (43). Our silencing experiments confirmed the key role of IRF-1 in ASM cells in driving the expression of GC-resistant chemokines via transcriptional (CCL5) and posttranscriptional mechanisms (CX3CL1).…”
Section: Discussionmentioning
confidence: 99%
“…The p38 MAPK pathway is a well known component of TNF signaling (46,47) and can also be regulated by SK1 (48 -50). Furthermore, this pathway can also affect chemokine expression, although the effects on RANTES vary depending on the cell type and stimulus (34,51,52). Consequently, as a first step, the role of p38 MAPK in RANTES regulation was determined utilizing the p38 MAPK inhibitor BIRB 796 (53).…”
Section: Sk1 Is Not Required For Tnf-mediated Activation Of Nf-b Repomentioning
confidence: 99%
“…In the TNF response, many transcription factors have been implicated in RANTES induction including NF-B and interferon regulatory factor 1 (29,30), and activator protein 1 and NF-AT in airway epithelial and smooth muscle cells, respectively (31). Moreover, upstream of transcription factors, other signaling cascades have been implicated in RANTES regulation such as JNK (32), ERK (33), and p38 MAPK (34). More recently, our group identified sphingolipids as regulators of RANTES through the acid sphingomyelinase/ acid ceramidase pathway (16).…”
mentioning
confidence: 99%
“…CCL5 is also known to be involved in the progression of atherosclerotic plaques [27]. CCL5 belongs to the CC chemokine family which also includes CCL2.…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 was also one of the cytokines elevated in the serum of MMD patients [7]. CCL5 has been associated with the progression of atherosclerosis, mediating smooth muscle cell activation and macrophage recruitment [27]. Polymorphisms in the CCL5 gene were associated with stroke risks [28, 29].…”
Section: Discussionmentioning
confidence: 99%